Relationships among socio-demographic factors, family characteristics and grandparent-grandchildren relationship quality with psychological well-being among the Malaysian elderly - A. Pandialagappan, Thamilselvi (2018)
Psychological well-being as one of the most important indicators of successful aging has received substantial attention in the gerontological literature. Prior studies show that factors influencing elderly’s psychological well-being are multiple and differ across cultures. The aim of this study was to examine the relationships between socio-demographic factors, family characteristics, and grandparent-grandchild relationship quality with psychological well-being among Malaysian elderly. The study included 600 grandparents aged between 41–93 years, selected through a multistage stratified random sampling method within Peninsular Malaysia. WHO-Five well-being index was used to measure psychological well-being. The descriptive study employed secondary data analysis which was collected for the purpose of Development and Testing of Grandparenting Stressor-Strength Inventory in Malaysia. Data analysis was conducted using the IBM SPSS version 22.0. Amongst the socio-demographic factors and family characteristics, grandparent’s (G1) age, ethnicity, marital status, health status, level of education, adult child’s (G2: father or mother of grandchild) marital status, parent-grandparent (G1-G2) relationship, grandchild’s (G3) age and birth order, grandparent-grandchild (G1-G3) relationship quality was significantly associated with psychological well-being at bivariate level. Using multiple regression analysis, a significant model emerged (F (10, 589) = 49.004, p < .001) where grandparent’s ethnicity, health status, educational level, adult child (G2) marital status, and grandparent-grandchild relationship quality were significant predictors of psychological well-being among Malaysian elderly. Moderated hierarchical regression analysis demonstrated that grandparent’s level of education significantly moderates the association between grandparent-grandchild relationship quality and psychological well-being, after controlling for ethnicity, health status and G2 marital status. For older Malaysians, higher educational level was found to enhance the association between their relationship quality with grandchildren and their psychological well-being. Therefore, policy makers, and practitioners who work with elderly people should give special attention on the health, educational level and intergenerational relationships in the family.